Prevention of Pediatric Acute Kidney Injury - Heeyeon Cho (Childhood Kidney Diseases, 2015)
The incidence of acute kidney injury (AKI) in critically ill pediatric patients has been reported as increasing to 25 %, depending on population characteristics. The etiology of AKI has changed over the last 10-20 years from primary renal disease to the renal conditions associated with systemic illness. The AKI in pediatric population is associated with increased mortality and morbidity, and prevention is needed to reduce the consequence of AKI. It is known that the most important risk factors for AKI in critically ill pediatric patients are clinical conditions to be associated with decreased renal blood flow, direct renal injury, and illness severity. Renal hypoperfusion leads to neurohormonal activation including renin-angiotensin-aldosterone system, sympathetic nervous system, antidiuretic hormone, and prostaglandins. Prolonged renal hypoperfusion can result in acute tubular necrosis. The direct renal injury can be predisposed under the condition of renal hypoperfusion, and appropriate treatment of volume depletion is important to prevent AKI. The preventable causes of AKI include contrast-induced nephropathy, hemodynamic instability, inappropriate mediation use, and multiple nephrotoxic insults. Given the evidence of preventable factors for AKI, several actions such as the use of protocol for prevention of contrast-induced nephropathy, appropriate treatment of volume depletion, vigorous treatment of sepsis, avoidance of combinations of nephrotoxic medications, and monitoring of levels of drugs should be recommended.